Muslim women diaspora in the west : a postcolonial feminist study of three post-9/11 British literary texts - Zebunnisa binti P. Mohamad Abdul Razak (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2017)
The aftermath of the 9/11 attacks has left Muslims with traces of strong resentment and bitterness. Biased perceptions held by mainstream society have increasingly impaired the image of Islam, resulting in the ill-conceived apprehension of Muslims in the contemporary age. The negative portrayal of Muslims through stereotyping and misrepresentations are a common phenomenon due to an exponential rise of Islamophobia in the West. Misleading notions of Islam are propagated by Western media in an orchestrated attempt to denigrate Islamic teachings. Consequently, an array of Muslim women writers have embarked on a journey of literary works based on their own experiences and a shared 'Muslim consciousness', which have created a platform to present the deplorable facts surrounding the Muslim diaspora in the West. Three such authors are Monica Ali (1967–), Leila Aboulela (1964–) and Fadia Faqir (1956–). Their works in relation to the issues concerned are Brick Lane (2003), Minaret (2005) and My Name is Salma (2007). This study will examine these works in order to understand the Muslim experience after 9/11, specifically Muslim women's path, strewn with many challenges, towards integration in Britain. Muslims who migrate to the West seem to pose an equally challenging experience. These 'Third World' women encounter a set of ordeals and obstacles as they migrate from their countries of origin. As such, the possibilities of Islamic values and practices and indigenous cultures being accepted in a mainstream Western society are discussed in relation to the new environment in which these women live.